Work won't love you back : how devotion to our jobs keeps us exploited, exhausted, and alone - Jaffe, Sarah, 1980- (Bold Type Books, 2021)
"You're told that if you "do what you love, you'll never work a day in your life." Whether it's working for "exposure" and "experience," or enduring poor treatment in the name of "being part of the family," all employees are pushed to make sacrifices for the privilege of being able to do what we love. In Work Won't Love You Back, Sarah Jaffe, a preeminent voice on labor, inequality, and social movements, examines this "labor of love" myth -- the idea that certain work is not really work, and therefore should be done out of passion instead of pay. Told through the lives and experiences of workers in various industries -- from the unpaid intern, to the overworked nurse, to the nonprofit worker and even the professional athlete -- Jaffe reveals how all of us have been tricked into buying into a new tyranny of work. As Jaffe argues, understanding the trap of the labor of love will empower us to work less and demand what our work is worth. And once freed from those binds, we can finally figure out what actually gives us joy, pleasure, and satisfaction"--